(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
This study provides a novel a system dynamics foundation for this next retail electricity industry (the "Energy Network") with both a large number of dispersed household electricity providers (the "Energy Cells"). The projected Energy Internet is intended to facilitate the development of something like a wide range of diverse renewable energy generating and storage devices using plug-and-play technology. By running and maintaining his respective regional generation, regional fuel cells, including distributed generation tasks locally, cable subscribers, also based on Energy Mitochondria, may be simultaneous consumers and providers of power. This work provides a collection of computer simulations of retailer electric industry players, despite a variety of local and worldwide restrictions. A statistical empirical study is undertaken using tournament methodologies to develop an efficient last retail power economic system. Your computational showed that the developed equilibrium wage approach is successful with a substantial penetration of distribute household power providers